2015
DOI: 10.1007/s13277-015-3898-9
|View full text |Cite
|
Sign up to set email alerts
|

Five miRNAs considered as molecular targets for predicting neuroglioma

Abstract: Neuroglioma is a complex neuroglial tumor involving dysregulation of many biological pathways at multiple levels. Here, we aim to screen differentially expressed miRNAs (DEMs) as well as the functions and pathways of their target genes in neuroglioma. miRNA high-throughput sequencing data were downloaded from The Cancer Genome Atlas (TCGA), and then the DEMs were subjected to perform principal component analysis (PCA) based on their expression values. Following that, Targetscan software was used to predict the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 28 publications
1
18
0
Order By: Relevance
“…Consistent with our expression results, a previous study by Xu and colleagues also found the decreased miR-1298 expression in NSCLC by a bioinformatics analysis [14]. In addition to NSCLC, the reduced miR-1298 expression has also been identified in patients with gastric cancer [24] and neuroglioma [25], indicating the tumor suppressor role of miR-1298 in tumorigenesis.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with our expression results, a previous study by Xu and colleagues also found the decreased miR-1298 expression in NSCLC by a bioinformatics analysis [14]. In addition to NSCLC, the reduced miR-1298 expression has also been identified in patients with gastric cancer [24] and neuroglioma [25], indicating the tumor suppressor role of miR-1298 in tumorigenesis.…”
Section: Discussionsupporting
confidence: 92%
“… 22 MiR-1911-3p has been reported to have a correlation with neuroglioma. 23 In addition to the two miRNAs, most identified DE-miRNAs have been confirmed to be associated with tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, abnormal expression of miR‐455 was reported in several human diseases (Ji et al, ; Zhang et al, ). Expression of miR‐455 is elevated in glioblastoma multiforme cells and osteoarthritis (Ujifuku et al, ; Swingler et al, ), but reduced in gastric cancer and neuroglioma (Dong et al, ; Yang and Wang, ). Importantly, upregulation of miR‐455 expression has been shown to suppress cell growth and metastases in melanoma and colorectal cancer (Chai et al, ; Shoshan et al, ).…”
Section: Discussionmentioning
confidence: 99%